Children of cross border marriage (CBM): Their rights and future - Md Hashim, Noraini; Che Soh @ Yusoff, Roslina; Abdul Hak, Nora; Mohd Helmi, Md Said (2017)
In a cross-border marriage (CBM), failure of the Muslim parties to register their CBM will have direct impact to their future born child. Their action will contravene with Articles 3, 5, 7 and 28 of United Nation Convention on Rights of Child that spell out that parents must do what is the best for their children, protect their rights, legally registered their name and right to education. The main purpose of this paper is to address that failure of the CBM couple to register their marriage, no certificate of marriage be produced, will ended up with failure to register the birth. Even if registration of birth is allowed, the name of the biological father will not be stated. Without birth certificate, the child cannot register at public school and lose his right to education. On the other hand, under hukum syara‘ the child paternity is in doubt and he might lose his right to inheritance if his father died. The study is vital to address to the public the importance of registering their marriage as not to jeopardize their child‘s future. This paper uses a qualitative data collection method where in-depth document analysis is carried out. Primary sources such as the Acts, Regulations and court‘s decision are scrutinised. On the other hand, secondary sources that are studied comprise of law reports, legal periodical articles and newspaper cuttings. Possible suggestions are offered in the conclusion.